Teaching and Learning English in Times of the Pandemic – A Case Study in a North-Macedonian Primary School - Rashit Emini; Sharon C. Lee (Journal of Linguistics and Language Teaching)
The worldwide spread of the coronavirus has caused a huge turmoil in people’s lives, significantly impacting the functioning of educational institutions which imposed a shift from traditional face-to-face teaching to online education. The situation has caused far-reaching changes in teaching and learning practices in all educational institutions worldwide. The current study investigates the impact of COVID-19 on teaching and learning English as a foreign language online during the pandemic in a primary school in Skopje, Republic of North Macedonia. Qualitative and quantitative research methods utilising questionnaires and interviews were used to collect data to reveal the viewpoints and attitudes of school authorities, teachers, and pupils concerning the teaching and learning of English on a virtual basis. Seventy-three 6th, 7th, 8th, and 9th-grade pupils, four teachers, and the headmistress of a primary school in Skopje voluntarily participated in this study. The research findings revealed that the pandemic caused a hugely negative impact on the teaching and learning process and it hindered the achievement of the expected learning outcome. Moreover, the school was unprepared for the pandemic; yet, the school managed to shift the mode of teaching and learning from an on-site to an online scenario very quickly, as neither teachers nor pupils had any previous experience with online teaching and learning, and both parties preferred the on-site to the online mode.